2022
DOI: 10.1038/s41598-022-07149-9
|View full text |Cite
|
Sign up to set email alerts
|

Functionally distinct T-helper cell phenotypes predict resistance to different types of parasites in a wild mammal

Abstract: The adaptive immune system is critical to an effective response to infection in vertebrates, with T-helper (Th) cells pivotal in orchestrating these responses. In natural populations where co-infections are the norm, different Th responses are likely to play an important role in maintaining host health and fitness, a relationship which remains poorly understood in wild animals. In this study, we characterised variation in functionally distinct Th responses in a wild population of Soay sheep by enumerating cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Furthermore, resistance to helminths is dependent on T helper type 2 (Th2) responses, which can be constrained by immune commitment to the Th1 responses required for resistance to microparasites such as coccidia (Graham, 2008 ). Recent evidence in wild Soay sheep has shown that Th1-associated immune phenotypes predicted reduced coccidian FOCs, while Th2-associated phenotypes predicted reduced strongyle FECs (Corripio-Miyar et al ., 2022 ). Although this supports the role of functionally distinct aspects of the immune response in controlling these two different parasite groups, we also found that sheep mounting strong Th1 responses also tended to mount strong Th2 responses (Corripio-Miyar et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, resistance to helminths is dependent on T helper type 2 (Th2) responses, which can be constrained by immune commitment to the Th1 responses required for resistance to microparasites such as coccidia (Graham, 2008 ). Recent evidence in wild Soay sheep has shown that Th1-associated immune phenotypes predicted reduced coccidian FOCs, while Th2-associated phenotypes predicted reduced strongyle FECs (Corripio-Miyar et al ., 2022 ). Although this supports the role of functionally distinct aspects of the immune response in controlling these two different parasite groups, we also found that sheep mounting strong Th1 responses also tended to mount strong Th2 responses (Corripio-Miyar et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence in wild Soay sheep has shown that Th1-associated immune phenotypes predicted reduced coccidian FOCs, while Th2-associated phenotypes predicted reduced strongyle FECs (Corripio-Miyar et al ., 2022 ). Although this supports the role of functionally distinct aspects of the immune response in controlling these two different parasite groups, we also found that sheep mounting strong Th1 responses also tended to mount strong Th2 responses (Corripio-Miyar et al 2022 ). It is possible that the immune responses that develop in sheep to coccidia during the first year of life are more effective than those against strongyle and that varied resource costs of anti-coccidian vs anti-strongyle responses may account for the varied effect of reproductive status on severity of infection.…”
Section: Discussionmentioning
confidence: 99%
“…When stimulated by antigens, immature DCs recognize, uptake, and process antigens, and gradually mature in the process of migration. Mature DCs present antigens to naive CD4 + T cells through the major histocompatibility complex-II (MHC-II), thereby enabling CD4 + T cells to be activated and to differentiate into different cell subsets that secrete various cytokines, resulting in different types of adaptive immune responses, such as Th1, Th2, Th17, and Tregs (Letendre et al, 2018;Corripio-Miyar et al, 2022). Under normal circumstances, IFN-γ secreted by Th1 and IL-4 secreted by Th2 antagonize each other to maintain immune balance in the body.…”
Section: Protein Accession Protein Descriptionmentioning
confidence: 99%
“…For wild non-model species, immunological analysis tools are often limited (5-7), and ethical considerations can limit study designs. Despite these difficulties, several studies have been performed recently to understand variation in T cell immune responses in wild mammals (8)(9)(10)(11)(12)(13). Further, pioneering studies have started to probe immune responses to parasite infection in M. m. domesticus in the wild (14) and laboratory mice released into outdoor enclosures (4).…”
Section: Introductionmentioning
confidence: 99%